A New Approach for Researching Victims: The ‘Strength-Growth-Resilience’ Framework - Green, Simon (The British journal of criminology, 2021)
This paper proposes a new framework for researching victims that blends appreciative inquiry methods used by prison researchers with narrative interview methods used by desistance researchers to investigate victim ‘strength-growth-resilience’. Alongside established victimological concerns with the extent, distribution and treatment of crime victims, this framework offers an alternative lens that focuses on victim agency, identity and transformation. Building on the emancipatory project of feminist victimology, narrative and cultural criminology and an emerging narrative victimology the framework aims to provide a new conceptual reference point for victimological research. The article’s objectives are to demonstrate that this framework delivers a theoretically, empirically and ethically robust approach for exploring the mechanisms by which victims become resilient, and can even flourish, in the aftermath of criminal harm.